Internet of things, for things, and by things - Chaudhuri, Abhik (CRC Press, Taylor & Francis Group, 2019)
This book discusses the necessary behavioral attributes for smart living and the policy implications necessary to develop it in order to help citizens be as ready as possible for smart living. It covers the aspect of defects in IoT design and implementation for cyber defense of Smart Services. Includes an indepth discussion of the role of strategic communication in creating safe and secure smart services, with privacy, security and trust. The book aims to help policy makers, engineers, and educators support an ethical, safe, and secure digitally-enhanced environment in which all can live smarter--